2022
DOI: 10.3390/ijms232213718
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Chemistry of Phosphate Groups in Systems Including Copper(II) Ions, Phosphoethanolamine and Pyrimidine Nucleotides

Abstract: The activity of phosphate groups of phosphoethanolamine and pyrimidine nucleotides (thymidine 5-monophosphate, cytidine 5-monophosphate and uridine 5’monophosphate) in the process of complexation metal ions in aqueous solution was studied. Using the potentiometric method with computer calculation of the data and spectroscopic methods such as UV-Vis, EPR, 13C and 31P NMR as well as FT-IR, the overall stability constants of the complexes as well as coordination modes were obtained. At lower pH, copper(II) ions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Chemical shifts between ligand and ligand in the complex on the 31 P NMR spectra are signi cant for cholP and CMP also (-2.55 ppm and − 2.08 ppm respectively). Taking into consideration values of the protonation constants logK e = 5.48 and 4.48 for cholP and CMP, respectively, we concluded that in the inner coordination sphere, only the oxygen atoms of phosphate group of CMP are involved, similar like for Cu(enP)H 4 (CMP) 24 . Some changes between shifts in 13 C NMR on C(2) and C(4) atoms and positions of the antisymetric stretching bands N-CH 3 from -N + (CH 3 ) 3 point to weak interactions between the ring of CMP as negative center and positively charged phosphocholine 31 .…”
Section: Spectroscopic Studies Of the Cu(ii)/cholp/nmp Systemsmentioning
confidence: 81%
See 1 more Smart Citation
“…Chemical shifts between ligand and ligand in the complex on the 31 P NMR spectra are signi cant for cholP and CMP also (-2.55 ppm and − 2.08 ppm respectively). Taking into consideration values of the protonation constants logK e = 5.48 and 4.48 for cholP and CMP, respectively, we concluded that in the inner coordination sphere, only the oxygen atoms of phosphate group of CMP are involved, similar like for Cu(enP)H 4 (CMP) 24 . Some changes between shifts in 13 C NMR on C(2) and C(4) atoms and positions of the antisymetric stretching bands N-CH 3 from -N + (CH 3 ) 3 point to weak interactions between the ring of CMP as negative center and positively charged phosphocholine 31 .…”
Section: Spectroscopic Studies Of the Cu(ii)/cholp/nmp Systemsmentioning
confidence: 81%
“…Hyperquad 2020 program was used to determine the protonation constants and stability constants of the complexes as described before 20,24,33 .…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that FMN/Fmoc-K/Cu 2+ also displayed two sets of EPR parameters (Table S2), but the g ∥ values were slightly higher than those of Fmoc-K/Cu 2+ . The higher g ∥ (also Δ g ) values indicate a weaker crystal-field strength, which could suggest that the phosphate groups in FMN are involved in binding with Cu 2+ . , In addition, we explored the influence of ligand concentrations on the EPR signal of Cu 2+ , and we found that FAD/Fmoc-K ratios or Fmoc-K concentrations did not affect the hyperfine parameters (Figure S4 and Table S2), reflecting that the coordination environment of Cu 2+ was almost unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the low mobility of copper ions in the electrospinning solutions, as they have an affinity to interact with negatively charged molecular groups, such as carbonyls. 30 Therefore, increasing the copper amount increases electrostatic interactions with the primary fiber chains (long and open polymer chains), resulting in lower electrical conductivity values. However, the solutions' viscosity and surface tension properties did not substantially change with the copper salt addition.…”
Section: Resultsmentioning
confidence: 99%
“…3cm2 were weighted and individually immersed in 25 mL ultrapure water at room temperature. A 0.5 mL aliquot was withdrawn over 24 h(5,15,30, 60, 120, 240, 480, 720, and 1440 min) and analyzed by flame AAS at 324.9 nm. The release test was performed in three different samples (triplicate), and the values were expressed in mg.g À1 .2.11 | Virucidal activity experimentsVirucidal properties of the virucidal composite membranes and control membrane (2 Â 2 cm 2 strip) were determined in vitro by coronavirus exposure of the MHV-3 Coronaviridae lineage which belongs to the betacoronavirus (β-CoV) genera, a surrogate SARS-CoV-1 and SARS-CoV-2,25,26 and murine fibroblast cell line (L929, ATCC ® CCL-1™).The L929 cells were grown in Dulbecco Minimum Eagle Essential Medium (DMEM) supplemented with 10% fetal bovine serum (FBS).…”
mentioning
confidence: 99%